Stroke in children and adolescents: topical problems of pre-hospital diagnostics - Y. A. Khachaturov; I. O. Shchederkina; N. F. Plavunov; A. M. Sidorov; E. E. Petryaykina; I. P. Vytkovskaya; V. A. Kadyshev (SINAPS LLC, 2020)
The article is devoted to the urgent problem of pediatrics and pediatric neurology, pre-hospital diagnosis of stroke in children. A review of domestic and foreign literature on the early diagnosis of stroke in children and adolescents, as well as epidemiological data on pediatric stroke, is presented. Particular attention is paid to the features of the symptoms of stroke and stroke-like conditions («stroke masks») in the pediatric population and the analysis of the main factors that influence errors in the early diagnosis of stroke in children and adolescents. Currently, in the diagnosis of ischemic stroke, its «masks» are found in 53.9 % of cases, with hemorrhagic stroke, in 36.3 %, and with transient ischemic attacks, in 9.8 % of cases. One of the most common diseases with which it is necessary to differentiate ischemic stroke in children is migraine. This problem is covered in academic writings that highlight the leading differential diagnostic criteria for migraine and stroke, and also represent a diagnostic algorithm. The clinical features of pediatric stroke, especially manifest symptoms, make it difficult to apply adult screening stroke scales in pediatrics. The article discusses the main scales for the early diagnosis of stroke in adults, and their potential application in pediatric practice. Currently accumulated experience in prehospital and early diagnosis of stroke in children determines the main directions of work to reduce the time of diagnosis of acute cerebrovascular accidents in children, followed by the introduction of reperfusion therapy in pediatric practice.